America’s Next Top Model: An analysis of the educational potential of a reality show about beauty - Atarama Rojas, Tomás (2015)
The presence of beauty in society has now a leading role thanks to the relevance that social media has given it. There is a tendency to elaborate reality TV shows based on beauty. This article analyses the comments of the judges of America’s Next Top Model Season 19th to discover if the message in this show can be transmitted as a positive message in a time where reality shows are cataloged as low quality television. After a hard analysis of the season, we can say that the value of the beauty for the jury is the one learn during the contest.